A new parallel matrix multiplication algorithm on distributed-memory concurrent computers - Choi, Jaeyoung (Concurrency (Chichester, England.), 1998)
We present a new fast and scalable matrix multiplication algorithm called DIMMA (distribution‐independent matrix multiplication algorithm) for block cyclic data distribution on distributed‐memory concurrent computers. The algorithm is based on two new ideas; it uses a modified pipelined communication scheme to overlap computation and communication effectively, and exploits the LCM block concept to obtain the maximum performance of the sequential BLAS (basic linear algebra subprograms) routine in each processor even when the block size is very small or very large. The algorithm is implemented and compared with SUMMA on the Intel Paragon computer. © 1998 John Wiley & Sons, Ltd.